Trends toward the concentration of economic activity and uneven spatial development of Russia - Anna Bufetova (European Regional Science Association (ERSA), 2016)
The introduction of market mechanisms regulating the economy in the Russian Federation has led to change of spatial distribution of economic activity and further increase of regional economic development disparities. All the approaches to the regional policy declared by the Government in the last decades didn't succeed. So the question of evolution of spatial distribution of economic activity and regional disparities remains very actual. The aim of this work was to analyze the evolution of spatial distribution of economic activity in the Russian Federation and the role of space in the inequality of regional development. We study the evolution of spatial distribution of economic activity and convergence process among regions from the change of the region relative position inside the cross-sectional distribution of regions in terms of gross regional product (GRP). The growth process is modeled as a first-order Markov chain. Spatial effects in our study are introduced within the Markov chain framework using regional conditioning and spatial Markov chain. By applying this technique we achieve a more detailed picture of the evolution of distribution of economic activity and spatial disparities than in other studies on the topic. These tools also allow studying how the economic performance of a region and its position inside the GRP distribution can be explained by its geographical environment. The results of the analysis, based on a data set for 79 Russian regions over 2001-2013 period suggest that the process of economic growth has been characterized by the continuing concentration of economic activity. Along with the preservation and strengthening of positions of the former centers, a number of new ones emerged, and at the same time some centers with resource specialization to some extent weakened their positions. The study showed a progressive bias toward a poverty trap. The ergodic distribution of the regions in terms of economic activity, achievable while maintaining trends of study period, shows the formation of a sufficiently large pole of relative poverty and pole of wealth that concentrates a significant proportion of manufacturing value added. Emerging group of regions with an average level of development is relatively small. Regional conditioning and spatial Markov chain clearly indicate that location and physical geography matter to explain growth and convergence process. The changes of the relative position of a region in the cross-sectional distribution are highly constrained by its geographical environment. Regions of almost all level of development have better evolutionary perspectives when surrounded by rich neighbors (but not less developed regions) and worse perspectives when surrounded by poor neighbors so that progressive bias towards poverty trap has a strong spatial explanation. In such circumstances, regional policy aimed at stimulating the developed regions, can reinforce the ongoing process of polarization. And policy aimed at smoothing the uneven territorial development in order to avoid excessive deepening of regional disparities and inequalities seems to be more adequate.
Keywords: R11; R12; 330; spatial distribution of regional economic activity; regional disparities; Markov chains